Anaerobic digestion of by-products of sugar beet and starch potato processing - Kryvoruchko, Vitaliy; Machmüller, Andrea; Bodiroza, Vitomir; Amon, Barbara; Amon, Thomas (Biomass & bioenergy, 2009)
Anaerobic digestion (AD) is a promising option for the environmentally friendly recycling of agricultural by-products. However, overloading of the digester with sugar, starch or protein might cause inhibition of the anaerobic processes. The aim of the present project was to investigate the AD of sugar beet, starch potato by-products and effect of pre-treatment by steam on methane yield of potatoes pulp. The investigated by-products have been: sugar beet pulp silage (SBP), sugar beet tail silage (SBT), potato pulp (PP), potato peel pulp (PPP) and potato fruit water (PFW). All by-products were digested in 1 l eudiometer-batch digesters at 37.5 °C during 28–38 days. The specific methane yields of SBP and SBT were 430 and 481 l N kg −1 volatile solids (VS), respectively. The specific methane yields of PP, PPP and PFW were 332, 377 and 323 l N (kg VS) −1. A steam pre-treatment significantly increased the specific methane yield of PP up to 373 l N (kg VS) −1.